Geochemical and Geochronological Constraints on the Origin and Emplacement of the East Taiwan Ophiolite. (30th April 2019) - Lin, Chiou‐Ting; Harris, Ron; Sun, Wei‐Dong; Zhang, Guo‐Liang
Abstract: The East Taiwan Ophiolite (ETO) occurs as blocks and thrust sheets associated with the Lichi Mélange in the Coastal Range of eastern Taiwan. The blocks consist of serpentinized harzburgite, serpentinite breccia, gabbro, dikes of dolerite and plagiogranite, pillow basalts, and red clay within a mud‐ and serpentinite‐rich mélange matrix. New U‐Pb zircon dating of a pegmatite gabbro yields a weighted mean age of 16.65 ± 0.20 Ma. This age is earlier than the North Luzon Arc but overlaps with the late‐stage spreading of the South China Sea. ETO glassy basalt has low K2 O, MgO and high CaO contents, similar to MORB. REE and trace element patterns show both N‐MORB patterns with LREE depletion and E‐MORB patterns with slight LREE enrichment. A few samples show slight depletion in Nb‐Ta and Ti and enrichment in Rb, Ba, U and Sr, indicating a hint of subduction influence. Most ETO basalt plots within the overlapping fields of N‐MORB and BABB on Ti‐V, Cr‐Y, Nb/Yb‐Th/Yb, and Hf/3‐Th‐Ta discrimination diagrams. These geochemical compositions are emblematic of mid‐ocean ridge or back‐arc lava, like South China Sea basalt. We interpret ETO basalt and gabbro as fragments of the subducted South China Sea basement that were scrapped off and accreted to the Luzon forearc during the process of subduction initiation along the Manila Trench. Blocks of mantle material in the mélange may originate from the upper plate of the arc‐continent collision and were mixed with lower plate crustal material in a subduction channel now represented by the Lichi Mélange. Key Points: The geochemical composition of the ETO basalt is similar to MORB/BABBs affinities and shows a kinship of the South China Sea The ETO basalt could be accreted to the forearc from the downgoing oceanic lithosphere during subduction initiation along the Manila Trench The East Taiwan Ophiolite is a composite ophiolite mixed from both lower and upper oceanic fragments